Bidirectional cargo transport: Moving beyond tug-of-war - Hancock, William O. (Nat Rev Mol Cell Biol, 2014)
Vesicles, organelles and other intracellular cargo are transported by kinesin and dynein motors, which move in opposite directions along microtubules. This bidirectional cargo movement is frequently described as a “tug-of-war” between oppositely-directed motors attached to the same cargo. However, although many experimental and modeling studies support the tug-of-war paradigm, numerous knockout and inhibition studies in a variety of systems have found that inhibiting one motor leads to diminished motility in both directions, which is a “paradox of codependence” that challenges it. In an effort to resolve this paradox, three classes of bidirectional transport models, termed microtubule tethering, mechanical activation, and steric disinhibition, are proposed and a general mathematical modeling framework for bidirectional cargo transport is put forward to guide future experiments.